2015
DOI: 10.15386/cjmed-421
|View full text |Cite
|
Sign up to set email alerts
|

Management of endometrial modifications in perimenopausal women

Abstract: Perimenopause has a variable length and time of onset and is characterized by its variability in hormonal levels. The histological changes in the perimenopausal endometrium may be represented by nonproliferative or proliferative benign or malignant lesions. A commonly encountered manifestation of endometrium lesions during menopausal transition is the abnormal uterine bleeding (AUB). The clinical management of AUB must follow a standardized classification system for optimal results. The medical and surgical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 113 publications
0
19
0
1
Order By: Relevance
“…The period between the ages of 40 and 55 years corresponds to the perimenopause and is associated with the risk of iron deficiency anemia . This is associated with variations in hormonal levels and also menstrual disturbances with an increased risk of heavy bleeding . Moreover, an unhealthy lifestyle, often with restrictive dieting and a lack of exercise, was reported .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The period between the ages of 40 and 55 years corresponds to the perimenopause and is associated with the risk of iron deficiency anemia . This is associated with variations in hormonal levels and also menstrual disturbances with an increased risk of heavy bleeding . Moreover, an unhealthy lifestyle, often with restrictive dieting and a lack of exercise, was reported .…”
Section: Discussionmentioning
confidence: 99%
“…20 This is associated with variations in hormonal levels and also menstrual disturbances with an increased risk of heavy bleeding. 21 Moreover, an unhealthy lifestyle, often with restrictive dieting and a lack of exercise, was reported. 22 Although females of childbearing age are especially at risk F I G U R E 2 Prevalence of anemia according to age groups in both sexes of iron deficiency anemia due to menstrual iron loss, 23 females aged 40-49 years were found to be at a higher risk of anemia than females of childbearing age in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of ovarian cancer ranks first in gynecological tumors. Therefore, it is of great significance to improve the diagnosis and treatment of ovarian malignant tumors (10). There is no obvious symptom in the early stage of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have indicated that perimenopausal women with a diminished supply of FSH-responsive follicles experience intermittent ovulation or even chronic anovulation during this transition due to hormonal imbalance and menstrual irregularity (Nicula and Costin, 2015). Given our findings from mice that VCD (within a given concentration range) can function to promote oocyte maturation and to promote ovulation independent of FSH, it is of biological and clinical relevance to further examine whether VCD per se may be able to improve ovulatory responses and fertility in perimenopausal women.…”
Section: Discussionmentioning
confidence: 99%